A LysM Domain-Containing Gene OsEMSA1 Involved in Embryo sac Development in Rice (Oryza sativa L.) - Zhu, Qian; Zhang, Xiao-Ling; Nadir, Sadia; DongChen, Wen-Hua; Guo, Xiao-Qiong; Zhang, Hui-Xin; Li, Cheng-Yun; Chen, Li-Juan; Lee, Dong-Sun (Frontiers in Plant Science, 2017)
The embryo sac plays a vital role in sexual reproduction of angiosperms. LysM domain containing proteins with multiple lysin motifs are widespread proteins and are involved in plant defense responses against fungal chitins and bacterial peptidoglycans. Various studies have reported the role of LysM domain-containing proteins in plant defense mechanisms but their involvement in sexual reproduction remains largely unknown. Here, we report the involvement of a LysM domain-containing gene, EMBRYO SAC 1 (OsEMSA1), in the sexual reproduction of rice. The gene encoded a LysM domain-containing protein that was necessary for embryo sac development and function. The gene was expressed in root, stem, leaf tissues, panicle and ovaries and had some putative role in hormone regulation. Suppression of OsEMSA1 expression resulted in a defective embryo sac with poor differentiation of gametophytic cells, which consequently failed to attract pollen tubes and so reduced the panicle seed-setting rate. Our data offers new insight into the functions of LysM domain-containing proteins in rice.